O trabalho de campo em biogeografia - Homenagem ao Prof. Dr. Felisberto Cavalheiro (1945-2003) - Gerson de Freitas Junior (Confins)
Field work is in biogeography an important procedure of scientific research. In the following text, we sought to characterize the field work in general according to its importance in the process of research in geography (specifically for the branches of physical geography) and the training of geographers, and conceptualize them and highlight some of the specifics for the Biogeography.